ANALISIS PERLAKUAN AKUNTANSI TERHADAP RESTRUKTURISASI KREDIT BERMASALAH PADA PT. BANK SULUT - Lumempouw, Eliska Gricy; Poputra, Agus T.; Wokas, Heince R. N. (ACCOUNTABILITY, 2015)
All profit-oriented company, trying to minimize the expenses to maximize the profit. Similarly with a Commercial Bank in the region of North Sulawesi that is PT. Bank Sulut that is one of its main activities is to give credit to customers. The largest revenue in PT Bank Sulut derived from interest on loans to debtor. However, with the large amount of bad loans, the income would be reduced. In 2014 the amount of given credit by PT. Bank Sulut in the amount of IDR 6.875.354.000.000,- in September 2014 which has increased since March 2014 in the amount ofÂ  IDR 5.733.302.000.000,-. From the amount of given credit, PT. Bank Sulut charge for impairment losses on financial assets in the amount of IDR 85.078.000.000,- on September 2014 which in the amount of IDR 4.296.000.000,- before in March 2014. Due to the increase in that amount of given credits, the amount of impairment losses on financial assets affect profit of 0,07 % to 19,25 % (for period of March-September 2014. Calculation outside interest expense). Based on the phenomenon, this observation aimed to determine how the accounting treatment of restructuring of non-performing loan of PT. Bank Sulut. The Using Methods of this observation is descriptive-comparative analysis methods. Observation result point toward that PT. Bank Sulut has applied correctly for according to accounting provisions apply.